The structure and function of the radial mantle glands of Lyonsia hyattna (Bivalvia: Anomalodesmata)* - Prezant, Robert S. (Journal of Zoology, 1979)
Lyonsia hyalina Conrad possesses “radial mantle glands” of a complex structure located deep within the periostracal groove. They occur along the mantle edge in alignment with slightly raised striations of the periostracum, are deeply staining and are composed of three cell types. Secretory and supportive cells, which are flask-shaped, alternate throughout the gland, while a third cell type is ovoid and borders the gland. A sulfated mucopolysaccharide is secreted over the periostracum by the glands and functions in adhesion of sand grains to the shell.
Keywords: dept.aa